CRISPR-based knock-out of eIF4E2 in a cherry tomato background successfully recapitulates resistance to pepper veinal mottle virus. (March 2022) - Kuroiwa, Kyoka; Thenault, Christina; Nogué, Fabien; Perrot, Laura; Mazier, Marianne; Gallois, Jean-Luc
Highlights: CRISPR-Cas9 knockout of eIF4E2 gene was achieved in cherry-fruit tomato plants. This inactivation of eIF4E2 triggers genetic resistance to PVMV. CRISPR-Cas9 efficiently allows transfer of resistance to new cultivars. Abstract: The host susceptibility factors are important targets to develop genetic resistances in crops. Genome editing tools offer exciting prospects to develop resistances based on these susceptibility factors, directly in the cultivar of choice. Translation initiation factors 4E have long been known to be a susceptibility factor to the main genus of Potyviridae, potyviruses, but the inactivation of the eIF4E2 gene has only recently been shown to provide resistance to some isolates of pepper veinal mottle virus (PVMV) in big-fruit tomato plants. Here, using CRISPR-Cas9-NG, we show how eIF4E2 can be targeted and inactivated in cherry tomato plants. Three independent knockout alleles caused by indel in the first exon of eIF4E2, resulted in the complete absence of the eIF4E2 protein. All three lines displayed a narrow resistance spectrum to potyvirus, similar to the one described earlier for an eIF4E2 EMS mutant of M82, a big-fruit tomato cultivar; the plants were fully resistant to PVMV-Ca31, partially to PVMV-IC and were fully susceptible to two isolates of PVY assayed: N605 and LYE84. These results show how easily a resistance based on eIF4E2 can be transferred across tomato cultivar, but also confirm that gene redundancy can narrow the resistances based on eIF4E knockout.